2020
DOI: 10.3390/app10020641
|View full text |Cite
|
Sign up to set email alerts
|

The Carabattola—Vibroacoustical Analysis and Intensity of Acoustic Radiation (IAR)

Abstract: Among the studies of musical instruments, one important, sometime underestimated discipline, is represented by ethnomusicology. The acoustic analyses on ethnic musical instruments (M.I.) are much more infrequent if compared to those on classical M.I. This article deals with the vibro-acoustic analysis on one of the most unknown ethnic, Italian M.I., i.e., the carabattola (also called battola), which used to be played in Italy until the late 1960s during the Holy Thursday before Easter. The study includes modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The previous measurements, conducted by one of the authors on a kettledrum, have demonstrated the perfect matching between theoretical and experimental modal patterns. These results were also obtained during measurements on other musical instruments, as in Carabattola [18].…”
Section: Intensity Of Acoustic Radiation-iarsupporting
confidence: 67%
“…The previous measurements, conducted by one of the authors on a kettledrum, have demonstrated the perfect matching between theoretical and experimental modal patterns. These results were also obtained during measurements on other musical instruments, as in Carabattola [18].…”
Section: Intensity Of Acoustic Radiation-iarsupporting
confidence: 67%
“…These outcomes give an idea of their behavior in response to increasing demand for knowledge of those musical instruments. The second paper describes the outcome of an experimental analysis carried out on a carabattola, a largely unknown ethnic Italian musical instrument, which used to be played in the Romagna region until the Second World War [4]. The analysis includes modal analysis and IAR measurements.…”
Section: Musical Instruments: Acoustics and Vibrationmentioning
confidence: 99%
“…[15]- [20]. The relation between the modal behavior and the sound radiation is also studied for Western musical instruments like thar, si−thar and Santoor [21], [22]. Sound radiation studies other than those of the musical instruments exist [28], [29].…”
Section: Introductionmentioning
confidence: 99%